2017
DOI: 10.2147/ijn.s129436
|View full text |Cite
|
Sign up to set email alerts
|

siRNA-loaded poly(histidine-arginine)<sub>6</sub>-modified chitosan nanoparticle with enhanced cell-penetrating and endosomal escape capacities for suppressing breast tumor metastasis

Abstract: An ideal carrier that delivers small interfering RNA (siRNA) should be designed based on two criteria: cellular-mediated internalization and endosomal escape. Poly(histidine-arginine) 6 (H6R6) peptide was introduced into chitosan (CS) to create a new CS derivative for siRNA delivery, 6-polyarginine (R6) as cell-penetrating peptides facilitated nanoparticle cellular internalization has been proved in our previous research, and 6-polyhistidine (H6) mediated the nanoparticle endosome escape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 44 publications
0
43
0
Order By: Relevance
“…9R/DG-GNS (hydrazone) also showed uptake by tumor cells due to the targeting effect of DG. Positive 9R can bind the negative siRNA, used as a gene carrier [ 40 , 41 ], and it has been shown to have superior transmembrane transport ability [ 42 , 43 ]. In addition, the hydrazone bond was destroyed in the low endosomal pH microenvironment of tumor cells.…”
Section: Resultsmentioning
confidence: 99%
“…9R/DG-GNS (hydrazone) also showed uptake by tumor cells due to the targeting effect of DG. Positive 9R can bind the negative siRNA, used as a gene carrier [ 40 , 41 ], and it has been shown to have superior transmembrane transport ability [ 42 , 43 ]. In addition, the hydrazone bond was destroyed in the low endosomal pH microenvironment of tumor cells.…”
Section: Resultsmentioning
confidence: 99%
“…Combining chitosan with polyethylene glycol, the conjugate has a unique endocytosis and macrophage phagocytosis mechanism . In addition, the modification of chitosan with a polypeptide can improve its working efficiency (Ping et al, 2017).…”
Section: Polymer Micellar Co-delivery Systemmentioning
confidence: 99%
“…They are usually positively charged and can bind to negatively charged siRNA to improve its stability in vivo (Jiang et al 2015;Raucher and Ryu 2015;Jing et al 2016). From a review of in vivo studies, we observed three design variations of delivery systems involving cell-penetrating peptides: cellpenetrating peptides modified with chitosan and then used to encapsulate the siRNA (Sun et al 2017a); some studies entrapped or loaded a cell-penetrating peptide onto another primary delivery vehicle (such as liposomes or ultrasoundsensitive nanobubbles) (Jing et al 2016;Xie et al 2016); others conjugated a cell-penetrating peptide with other cationic polymers (such as PEG) or micelles to form a nanocomplex for siRNA encapsulation (Wang et al 2015;Fang et al 2016;Yang et al 2016). All in vivo studies demonstrated positive outcomes by showing that tumor growth was inhibited by siRNA.…”
Section: Cell-penetrating Peptidesmentioning
confidence: 99%